2021
DOI: 10.3390/antiox10081247
|View full text |Cite
|
Sign up to set email alerts
|

Aging under Pressure: The Roles of Reactive Oxygen and Nitrogen Species (RONS) Production and Aging Skeletal Muscle in Endothelial Function and Hypertension—From Biological Processes to Potential Interventions

Abstract: The proportion of adults living with hypertension increases significantly with advancing age. It is therefore important to consider how health and vitality can be maintained by the aging population until end of life. A primary risk factor for the progression of cardiovascular diseases (CVD) is hypertension, so exploring the factors and processes central to this burden of disease is essential for healthy aging. A loss of skeletal muscle quantity and quality is characteristic in normal aging, with a reduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 79 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies have confirmed the association between vascular aging and hypertension. 17,18 With the increase of physiological age, the structure and function of aging arteries gradually change, which was morphologically characterized by increased deposition of collagen fibres, disordered arrangement of smooth muscle cells and intimal thickening, and functionally manifested as increased stiffness and disturbed sensitivity to vasoconstrictor and diastolic factors. 19 These changes in the arteries would cause or aggravate hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed the association between vascular aging and hypertension. 17,18 With the increase of physiological age, the structure and function of aging arteries gradually change, which was morphologically characterized by increased deposition of collagen fibres, disordered arrangement of smooth muscle cells and intimal thickening, and functionally manifested as increased stiffness and disturbed sensitivity to vasoconstrictor and diastolic factors. 19 These changes in the arteries would cause or aggravate hypertension.…”
Section: Discussionmentioning
confidence: 99%